Efficacy and safety of peppermint oil for the treatment in Japanese patients with irritable bowel syndrome: a prospective, open-label, and single-arm study - Kei Matsueda; Shin Fukudo; Masayuki Ogishima; Yuki Naito; Soichiro Nakamura (BioPsychoSocial Medicine, 2024)
Abstract Background In Europe, an herbal medicine containing peppermint oil is widely used in patients with irritable bowel syndrome (IBS). In Japan, however, no clinical evidence for peppermint oil in IBS has been established, and it has not been approved as a drug for IBS. Accordingly, we conducted a clinical study to confirm the efficacy and safety of peppermint oil (ZO-Y60) in Japanese patients with IBS. Methods The study was a multi-center, open-label, single-arm, phase 3 trial in Japanese outpatients with IBS aged 17–60 years and diagnosed according to the Rome III criteria. The subjects were treated with an oral capsule of ZO-Y60 three times a day before meals, for four weeks. The efficacy of ZO-Y60 was evaluated using the patient’s global assessment (PtGA), IBS symptom severity score, stool frequency score, stool form score, and physician’s global assessment (PGA). The safety of ZO-Y60 was also assessed. Results Sixty-nine subjects were treated with ZO-Y60. During the four-week administration of ZO-Y60, the improvement rate of the PtGA was 71.6% (48/67) in week 2 and 85.1% (57/67) in week 4. It was also suggested that ZO-Y60 is effective against any type of IBS (IBS with constipation, IBS with diarrhea, and mixed/unsubtyped IBS). The improvement rate of the PGA was 73.1% (49/67) in week 2 and 85.1% (57/67) in week 4, also confirming the efficacy of ZO-Y60. Adverse events were observed in 14 subjects (20.3%), however, none of these adverse events were categorized as serious. Conclusion The efficacy of treatment was confirmed, subjective symptoms were improved, as was observed in previous clinical studies of ZO-Y60 conducted outside of Japan. All adverse reactions were previously known and were non-serious. These findings suggest that peppermint oil may be effective in the Japanese population and that it has an acceptable safety profile. Trial registration JAPIC Clinical Trials Information number: JapicCTI-121727 https://jrct.niph.go.jp/en-latest-detail/jRCT1080221685 . Registration date: 2012–01-10.